Strategi Kepala Desa Dalam Meningkatkan Kapasitas Perangkat Desa di Kalurahan Bangunjiwo, Kasihan, Bantul Daerah Istimewa Yogyakarta - Wawan Supriyanto,; Sugiyanto, Sugiyanto (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The problems faced by the village government of Bangunjiwo Kapanewon Kasihan, Bantul Regency and its officials are: (1) the capacity of the village administration is still lacking, the majority have SMA/K education, even though they are required to master information technology (IT) because they must be able to operate various applications; (2) regulations that often change in a short time which in the end makes the village apparatus become overwhelmed in implementing these regulations; and (3) there are still village officials who do not understand their duties and responsibilities. Based on these problems, the researchers conducted an analysis of the Bangunjiwo Village government's strategy in increasing the capacity of its apparatus, focusing on aspects of planning, implementing programs and activities, as well as evaluating programs and activities in increasing the capacity of the Bangunjiwo Village apparatus. The research approach is descriptive qualitative, with data collection techniques through interviews, observation, and documentation. The results of the study showed: (1) the Bangunjiwo Village Government had planned programs/activities to increase the capacity of village officials; (2) Implementation of programs/activities to increase the capacity of village officials in the form of: (a) sending delegations to attend training/workshops/seminars, and the like organized by the relevant agencies; (b) organize general training in the Bangunjiwo Sub-District, comparative studies to more developed/advanced sub-districts, or attend further studies at a Diploma Three or Bachelor program tertiary institution with financial facilities from the Kelurahan Expenditure Budget Plan; (3) Evaluation of programs/activities to increase the capacity of village apparatus by the Bangunjiwo Lurah internally, and externally by the Bangunjiwo Bamuskal. Obstacles/obstacles in increasing the capacity of the Bangunjiwo Village apparatus are the age of the majority of village officials who are over 50 years old, and budget constraints.